통신자료를 활용한 활동인구 연령계층의 혼합도 측정과 영향요인 : 서울시를 사례로 - 김슬기(Kim, Seulki); 고준호(Ko, Joonho) (국토계획, 2024)
다양한 연령층의 인구로 구성된 도시는 사회통합을 강화함과 동시에 노인인구의 복지를 증진시키는 등 도시와 시민의 번영을 도모한다. 이에 착안하여 활동인구 혼합지수의 의의를 고찰하고자, 본 연구에서는 서울시 생활이동 빅데이터를 활용하여 서울시 활동인구의 시간대별 연령계층의 혼합지수를 구하고, 혼합지수에 영향을 미치는 근린환경 요인을 산정하였다. 연구의 세부 목표는 다음과 같다. 첫째, 시간대별 활동인구의 연령대 구성 혼합지수를 분석하여혼합지수가 높은 행정동을 찾고, 행정동의 특징을 파악한다. 둘째, 선행연구를 참조하여 추출한 근린환경 특징이 활동인구 혼합지수에 얼마나 영향을 미치는지 분석한다. 최종적으로 본 연구의분석 결과를 바탕으로 연령별 사회통합에 대한 이해와 인구 혼합지수를 분석하는 새로운 개념을 제시한다. Social integration is promoted in urban areas where diverse age groups gather and interact, reducing risks such as elderly discrimination and isolation. The interaction between different age groups has benefits for social and mental health, and social integration has a positive impact on social stability by allowing populations from diverse ages, cultures, and economic backgrounds to coexist. Previous research on social population mixing in Korea has mainly focused on identifying problems with mixing patterns or estimating the effects of social integration through resident perception surveys. Furthermore, most studies have been limited to simple physical residential mixing, and research on age-specific mixing is relatively scarce compared to hierarchical analysis. Therefore, this study aims to measure age-specific mixing levels of hourly activity populations, by analyzing the influence of the built environment on mixing levels. This study’s results are expected to provide meaningful insights into spatial age segregation levels, beyond categorizing simple residential spaces. KCI Citation Count: 0